Association between Physical Activity Level and Sleep Quality in the Elderly - Nesya Kartika Dwi Cahya; Ignatio Rika (Journal of Urban Health Research, 2022)
Introduction: The increase in a person’s age may cause degeneration in their physiological system, and these changes can affect various bodily functions, one of them is the sleep-wake cycle. The elderly usually have disturbed sleep-wake circadian rhythm that can cause sleep problems and decreased sleep quality. The action that can be done to increase sleep quality is doing physical activity. Methods: This research used cross-sectional study design. The respondents were people who reside in Komplek Taman Pulo Indah and Perumahan Aneka Elok aged 60 and older and were not included in the exclusion criteria (n = 204). The instruments used were the Baecke questionnaire to measure physical activity level and the PSQI questionnaire to measure sleep quality. Data analysis was done in univariate and bivariate using chi-square test with significance level of p<0.005. Results: The prevalence of elderly with low physical activity levels and good sleep quality was 33.8%. Meanwhile, elderly with moderate physical activity levels and good sleep quality was 50%, and elderly with high physical activity levels and good sleep quality was 64,7%. Chi-square test was carried out and resulted in p = 0.002 (p<0.005), which meant the null hypothesis was rejected. Conclusions: There was an association between physical activity level and sleep quality in the elderly.